Evaluation of Heavy Metals in Water from a Post-Remediated Crude Oil Produced Water Discharge Channel in the Niger Delta - Asibor, Godwin; Gaja, Caroline; Edjere, Oghenekohwiroro (European Journal of Applied Sciences, 2025)
This study was carried out to evaluate heavy metals in a post remediated crude oil produced water discharge channel. A total of twenty water samples were collected from ten sampling locations using grab sampling technique in October, 2022 (wet season) and February, 2023 (dry season). Heavy metals were determined in all the samples using atomic absorption spectrophotometry after digestion with aqua regia. The results showed that the concentrations (mg/L) for heavy metals in the water for all locations and seasons ranged from <0.001-0.05 for Cd, 0.04-0.28 for Pb, 0.002-0.09 for Cr, 0.03-0.22 for Ni, 0.01-0.07 for Cu, <0.005-0.007 for V, 0.01-0.18 for Mn, 0.04-0.14 for Zn and 0.58-6.71 for Fe for all locations and seasons. The results showed that there was no significant (p > 0.05) spatial variation in the concentrations of all the heavy metals in the water but there was significant (p < 0.05) seasonal variation. Analysis of Variance (ANOVA) showed that there was no significant (p > 0.05) spatial variation in the concentrations of the heavy metals in the wet season (WS) and dry season (DS), however, t-test analysis showed that there was significant (p < 0.05) seasonal variation in the concentrations of the heavy metals. The heavy metals were significantly higher in the dry season than the wet season except for Cu, V and Fe which have higher in the dry season. On the average, the concentrations of the heavy metals in the water decrease in the order of Fe > Mn > Zn > Cu = Ni > Pb > V > Cr > Cd > As = Hg during the wet season and Fe > Pb > Ni > Mn > Zn > Cr > Cd = Cu > V > As = Hg during the dry season. The concentrations of the heavy metals except, Pb, Ni and Fe in the water samples were below or within their regulatory limits indicating recovery of the post remediated channel. This should be sustained to ensure full recovery of the remediated channel.